Variations in flanking or less conserved positions of Reb1 and Abf1 consensus binding sites lead to major changes in their ability to modulate nucleosome sliding activity - Fernanda Raiqueo; Roberto Amigo; José L. Gutiérrez (Biological Research)
Abstract Background Maintenance of nucleosome-free regions at gene regulatory regions conform a relevant aspect within chromatin dynamics. In the yeast Saccharomyces cerevisiae, Reb1 and Abf1 are among the transcriptions factors that perform this molecular function. These factors are thought to act as a barrier to nucleosome sliding that chromatin remodeling complexes such as ISW1a perform towards this region, being binding affinity a critical feature to act as a barrier. In this regard, sequence variations at positions flanking transcription factor binding sites could affect DNA shape features and, in turn, binding strength. In addition, recent studies have shown that positions of low conservation and/or flanking sequences might vary from gene bodies to gene regulatory regions. Considering these issues, we aimed to analyze whether variations in flanking or less conserved positions of Reb1 and Abf1 target sequences affect their binding affinity, especially dwell time, and their ability to hinder ISW1a’s sliding activity. Results We found that sequence changes at these positions deeply affect binding strength, particularly dwell time, and the ability to hinder ISW1a’s sliding activity. Importantly, even under conditions where a markedly higher transcription factor concentration for a weak binding site was used to compare it to a strong binding site under an equal binding saturation level, the strong site displayed a significantly higher ability to hinder sliding activity. Moreover, genome-wide analyses showed that the sequence variants of Reb1 and Abf1 binding sites conferring this ability to hinder sliding activity to these factors are enriched at promoter regions relative to gene bodies. Conclusions Our findings show that dwell time is a key feature to hinder nucleosome sliding activity. For Reb1 and Abf1 factors, sequence variation at less conserved positions of their binding sites strongly affects this feature. The differential frequency at these positions found at promoter regions, relative to gene bodies, highlights the relevance of including this type of comparison in certain strategies used to determine the consensus binding site for transcription factors. To determine the molecular functions that require long dwell times and the transcription factors responsible for these tasks will significantly contribute to untangle the grammar of cis-regulatory elements.